Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                
0% found this document useful (0 votes)
4 views

FunctionPracticeProblems

The document contains a series of function practice problems from various AHSME/AMC/AIME competitions, each with detailed solutions. It covers topics such as polynomial evaluation, root properties, and symmetry in functions. Key points for solving function-related problems are also summarized at the end.

Uploaded by

Rana Mukherjee
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
0% found this document useful (0 votes)
4 views

FunctionPracticeProblems

The document contains a series of function practice problems from various AHSME/AMC/AIME competitions, each with detailed solutions. It covers topics such as polynomial evaluation, root properties, and symmetry in functions. Key points for solving function-related problems are also summarized at the end.

Uploaded by

Rana Mukherjee
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
You are on page 1/ 8

Function Practice Problems from old AHSME/AMC/AIME

2
1) (1993 AHSME #12) If 𝑓 (2𝑥 ) = , for all x > 0, what is 2f(x)?
2+𝑥

Solution
𝑥 2 2 4 𝟖
Plug in x/2: 𝑓 (2( )) = 𝑥 = 2(2)+𝑥 = . Thus, 2f(x) = .
2 2+2 𝑥+4 𝒙+𝟒
2

2) (1995 AHSME #14) If f(x) = ax4 – bx2 + x + 5 and f(-3) = 2, then what
is f(3)?

Solution
f(-3) = a(-3)4 – b(-3)2 + -3 + 5 = 2, so 81a - 9b + 2 = 2 → 81a-9b = 0
f(3) = a(3)4 – b(-3)2 + 3 + 5 = 81a – 9b + 8 = 0 + 8 = 8
f(3) = 8.

3) (1988 AHSME #15) If a and b are integers such that x2 – x – 1 is a


factor of ax3 + bx2 + 1, then what is b?

Solution
For some function f(x), we have: ax3 + bx2 + 1 = (x2 – x – 1)f(x)

Notice that for the first term to match, f(x) = ax + c, for constants a and c:

ax3 + bx2 + 1 = (x2 – x – 1)(ax+c)


ax3 + bx2 + 1 = ax3 – ax2 – ax + cx2 – cx – c
ax3 + bx2 + 1 = ax3 + (c– a)x2 – (a+c)x – c

Equate coefficients.
When equating the constant coefficients we have +1 = -c, so c = -1.
When equating coefficients for x we have 0 = -(a+c), so c = -a, a = 1
When equating coefficients for x2 we have b = c – a = -1 – 1 = -2.
Thus, b = -2.
4) (1984 AHSME #16) The function f(x) satisfies f(2 + x) = f(2 – x) for
all real numbers x. If the equation f(x) = 0 has four distinct real roots, what
is the sum of those roots?

Solution
Let two of those distinct roots be a and b, where both a > 2 and b > 2. If a
is a root greater than 2, then we can write f(a) = f(2 + x), so a = 2 + x and
x = a – 2. 0 = f(2 + x) = f(2 – x) = f(2 – (a – 2)) = f(4 – a).

Thus, if a is one root, 4 – a is another distinct root.


Similarly, if b is one root, 4 – b is another distinct root.
Thus, the sum of these four roots must be a + (4 – a) + b + (4 – b) = 8.

5) (1983 AHSME #18) Let f be a polynomial function such that for all
real x, 𝑓 (𝑥 2 + 1) = 𝑥 4 + 5𝑥 2 + 3. For all real x, what is 𝑓 (𝑥 2 − 1)?

Solution
There exist constants a and b such that

𝑓 (𝑥 2 + 1) = (𝑥 2 + 1)2 + 𝑎(𝑥 2 + 1) + 𝑏 = 𝑥 4 + 5𝑥 2 + 3

𝑥 4 + 2𝑥 2 + 1 + 𝑎𝑥 2 + 𝑎 + 𝑏 = 𝑥 4 + 5𝑥 2 + 3

𝑥 4 + (2 + 𝑎)𝑥 2 + (𝑎 + 𝑏 + 1) = 𝑥 4 + 5𝑥 2 + 3

Equate the coefficient for x2, so we have 2 + a = 5, so a = 3.


Equate constant coefficients, so we have a + b + 1 = 3. Since a=3, b=-1.
It follows that f(x) = x2 + 3x -1.

Thus, 𝑓(𝑥 2 − 1) = (𝑥 2 − 1)2 + 3(𝑥 2 − 1) − 1


= 𝑥 4 − 2𝑥 2 + 1 + 3𝑥 2 − 3 − 1 = 𝒙𝟒 + 𝒙𝟐 − 𝟑.
6) (1999 AHSME #17) Let P(x) be a polynomial such that when P(x) is
divided by x – 19, the remainder is 99, and when P(x) is divided by x –
99, the remainder is 19. What is the remainder when P(x) is divided by (x
– 19)(x – 99)?

Solution
There exists polynomials S(x) and T(x), with T(x) being degree one such
that:

P(x) = S(x)(x – 19)(x – 99) + T(x)

We know that P(19) = 99 and P(99) = 19.

P(19) = S(19)(0) + T(19) = 99


P(99) = S(99)(0) + T(99) = 19

We also know that T(x) = ax + b, for constants a and b, since T(x) has to
be a function with a degree lower than (x – 19)(x – 99).

T(19) = 19a + b = 99
T(99) = 99a + b = 19

Subtract top equation from bottom to yield 80a = - 80, a = -1, b = 118
Thus, the remainder is –x + 118.

𝑥 1 𝜋
7) (1991 AHSME #21) If 𝑓 ( ) = , for all 𝑥 ≠ 0,1,1 and 0 < 𝜃 < ,
𝑥−1 𝑥 2
then what is 𝑓(𝑠𝑒𝑐 2 𝑥)?

Solution
1 1
𝑓 (1 + )=
𝑥−1 𝑥

I need to figure out what to plug into the expression inside of the f to
make it equal to x.
So we want to solve for y in terms of x in the equation below.

1
𝑥 = 1+
𝑦−1
1
𝑥−1 =
𝑦−1
1
𝑦−1 =
𝑥−1
1
𝑦 = 1+
𝑥−1

So,
1 1
𝑓 (1 + )=
1 1
1+ −1 1+
𝑥−1 𝑥−1
1 1 𝑥−1
𝑓 (𝑥 ) = = =
1 𝑥−1+1 𝑥
1+
𝑥−1 𝑥−1

Now we can solve for 𝑓(𝑠𝑒𝑐 2 𝑥):

2 2
𝑠𝑖𝑛𝑥
𝑠𝑒𝑐 𝑥 − 1 𝑡𝑎𝑛 𝑥 𝑡𝑎𝑛𝑥
𝑓(𝑠𝑒𝑐 2 𝑥 ) = = =( )2 = ( 𝑐𝑜𝑠𝑥 )2
𝑠𝑒𝑐 𝑥2 2
𝑠𝑒𝑐 𝑥 𝑠𝑒𝑐𝑥 1
𝑐𝑜𝑠𝑥
𝑠𝑖𝑛𝑥𝑐𝑜𝑠𝑥 2
=( ) = 𝑠𝑖𝑛2 𝑥
𝑐𝑜𝑠𝑥
8) (1986 AHSME #24) Let p(x) = x2 + bx + c, where b and c are integers.
If p(x) is a factor of both x4 + 6x2 + 25 and 3x4 + 4x2 + 28x + 5, what is
p(1)?

Solution
If p(x) is a factor of both polynomials it would also be a factor of 3f(x) –
g(x).

3f(x) = 3x4 + 18x2 + 75


4 2
-g(x) = 3x + 4x + 28x + 5
---------------------------------
3f(x)-g(x) = 14x2 – 28x + 70 = 14(x2 – 2x + 5)

p(x) must divide into 14(x2 – 2x + 5) evenly, which means that p(x) = x2
– 2x + 5. It follows that p(1) = 1 – 2 + 5 = 4.

9) (2003 AMC A #20) If f(x) = ax3 + bx2 + cx + d and f(-1) = 0, f(0) = 2


and f(1) = 0, what is b?

Solution
f(-1) = -a + b – c + d = 0
f(0) = d=2
f(1) = a + b + c + d = 0

f(-1) = -a + b – c + 2 = 0
f(1) = a + b + c + 2 = 0

Now add the two equations:

f(-1) + f(1) = 2b + 4 = 0. It follows that b = -2.


10) (1993 AIME #5) Let P0(x) = x3 + 313x2 – 77x – 8. For integers n ≥ 1,
define Pn(x) = Pn-1(x - n). What is the coefficient of x in P20(x)?

Solution
Pn(x) = Pn-1(x - n) = Pn-2(x – n – (n – 1)) = … P0(x – (n + (n-1)+…1))

𝑛(𝑛+1)
Pn(x) = 𝑃0 (𝑥 − )
2

20(21)
So, P20(x) = 𝑃0 (𝑥 − ) = 𝑃0 (𝑥 − 210)
2

𝑃0 (𝑥 − 210) = (𝑥 − 210)3 + 313(𝑥 − 210)2 − 77(𝑥 − 210) − 8

Now, we must find the coefficient of x in what is above:

3(210)2 – 2(313)(210) – 77

(630) (210) – (626)(210) – 77 = (210)(630 – 626) – 77 = 4(210) – 77 =


840 – 77 = 763.

11) (1986 AIME #11) The polynomial 1 – x + x2 – x3 + … + x16 – x17 may


be written in the form 𝑎0 + 𝑎1 𝑦 + 𝑎2 𝑦 2 + ⋯ + 𝑎17 𝑦17 , where y = x+1
and all the ai’s are constants. Find the value of a2.

Substitute y = x + 1, means that x = y – 1:

f((y-1)) = 1 - (y-1) + (y-1)2 - (y-1)3 + … + (y-1)16 - (y-1)17

Notice that –(y-1) = 1 – y, so we have


f(1-y) = 1 + (1 – y) + (1 – y)2 + (1 – y)3 + … + (1 – y)17

𝑘
Coefficient of y2 = ∑17
𝑘=2 ( )
2
Using the hockey stick identity by repeatedly applying Pascal’s Triangle
18 18×17×16
we find that this sum equals ( ) = = 3 × 17 × 16 = 𝟖𝟏𝟔.
3 6

Exercise left to the reader: Use induction on n to prove the following for
all integers greater than or equal to a. (Note: a is a fixed integer.)
𝑛
𝑘 𝑛+1
∑( )=( )
𝑎 𝑎+1
𝑘=𝑎
Functions – Some Key Points

1) You can plug in anything you want for x in f(x) to obtain the
information that you need.

2) Exploit the fact that x2n = (-x)2n, when evaluating f(x) and f(-x). So, of
you are give f(x) and most of the terms have even powers, it helps you
find f(-x), since those even powered terms stay the same.

3) When you have two different expressions for the same polynomial,
equate coefficients.

4) When there is a vertical line of symmetry, roots come in pairs (except


if the line of symmetry contains a root. Thus, the sum of the roots is
whatever that line of symmetry is (x = c for some constant c) times the
number of roots.

5) When given that the remainder of P(x) divided by x – r is q, this means


that P(r) = q.

6) Just like with integers, if a polynomial divides into two other


polynomials, it also divides into any linear combination of those two
polynomials.

You might also like